Brand Awareness dan Perceived Quality Mempengaruhi Loyalitas Pasien pada Rumah Sakit Khusus Mata Prima Vision Medan - Muhammad Faridz Syahrian; Eki Novaliza Angelina; Wienaldi Wienaldi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
This research aims to determine the influence of Brand Awareness and Perceived Quality on Patient Loyalty at the Prima Vision Special Eye Hospital, Medan. The population in this study were patients at the Prima Vision Medan Special Eye Hospital. The sample in this study was 93 patients at the Prima Vision Special Eye Hospital in Medan using the Slovin formula and the Simple Random Sampling method. The data analysis method used is descriptive analysis and multiple linear regression analysis. The research results show that simultaneously, Brand Awareness and Perceived Quality have a significant effect on Patient Loyalty at the Prima Vision Special Eye Hospital, Medan. Partially, Brand Awareness has a positive and significant effect on Patient Loyalty at Prima Vision Medan Special Eye Hospital, Perceived Quality has a positive and significant effect on Patient Loyalty at Prima Vision Medan Special Eye Hospital. From the results of the determinant coefficient analysis, it was obtained that R Adjusted Square (R^2) was 0.592, this means that 59.2 percent of the Patient Loyalty variable can be explained by the Brand Awareness and Perceived Quality variables while the rest can be explained by other variables not examined in this research.